2016
DOI: 10.1039/c6cc04090j
|View full text |Cite|
|
Sign up to set email alerts
|

Photoswitchable ring-opening polymerization of lactide catalyzed by azobenzene-based thiourea

Abstract: The reactivity of a catalytic polymerization system using photoresponsive azobenzene-based thiourea/PMDETA as a catalyst could be switched between slow and fast states by alternating exposure to UV and ambient light, because the active site of azobenzene thiourea is blocked via intramolecular hydrogen bonding when the azobenzene thiourea transfers from the E isomer to the Z isomer under UV irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Although the reversible light‐induced switchability was demonstrated, compound 21 revealed to be inactive in the catalysis of the polymerization of lactide. Therefore, a variant of 21 was proposed, namely compound 22 (Figure ) . In this case, the nitro substituent in the Z isomer engages in intramolecular H‐bonds with the thiourea moiety.…”
Section: Configurational Selection Following H‐bonding Complexes Formmentioning
confidence: 99%
“…Although the reversible light‐induced switchability was demonstrated, compound 21 revealed to be inactive in the catalysis of the polymerization of lactide. Therefore, a variant of 21 was proposed, namely compound 22 (Figure ) . In this case, the nitro substituent in the Z isomer engages in intramolecular H‐bonds with the thiourea moiety.…”
Section: Configurational Selection Following H‐bonding Complexes Formmentioning
confidence: 99%
“…A photoisomerizable organocatalyst, an azobenzene-based thiourea, was developed for the polymerization of rac-LA. 132 Therein, Wu and coworkers found that when the E isomer (39 E ) (Scheme 6b) is used, the coordination site is open and polymerizations reach 90% monomer conversion in 24 h. Upon UV irradiation (330−400 nm), isomerization to the analogous Z isomer 39 Z occurs, leading to a drastic decrease in polymerization activity compared with 39 E (k = 2.08 × 10 −4 vs 2.08 × 10 −3 min −1 , respectively). This change in catalytic activity was hypothesized to result from the intramolecular hydrogen bonding between the nitro group and the urea of 39 Z , which blocks the active site from monomer coordination.…”
Section: Photochemical Controlmentioning
confidence: 99%
“…In a similar vein, 12 was later used as a photoswitchable catalyst in the ring-opening polymerization of lactide. 23…”
Section: Photoswitchable Bifunctional Catalystsmentioning
confidence: 99%